(untitled) (Spectrum, 2022)
Trauma studies as a discipline came to prominence in the 1990’s. Though Sigmund Freud’s theories constitute its foundation, the eclectic nature of it provides scope for including post-structural, postcolonial, narrative, and sociocultural theories to analyze texts. It analyses the influence of trauma in culture and society and the ways through which trauma is represented. American author Toni Morrison has always been pivotal in representing the subjugation, torture and trauma inflicted upon her African-American community through her works. Apart from that, her works intend to retrieve the forgotten and discredited history of African-Americans in her writings. In “Recitatif,” she explores the institution of racism in an innovative way: her protagonists, Twyla and Roberta, belong to two different ethnicities but she keeps their racial identities concealed by not attaching any racial codes to anyone. While identifying the characters’ ethnicities, the readers come to face their own biases. Simultaneously, they also register the traumatic nature of the narrative. This paper intends to explore “Recitatif” in the light of trauma studies. By doing so, it will delineate Morrison’s view regarding the different modes of trauma that afflict the lives of African-American people. Spectrum, Volume 16, June 2021: 230-243